The Growing Gap Between Policy, Official Claims and Classroom Realities: Insights from Colombian Mathematics Teachers´ Conceptions of Beginning Algebra and its Teaching Purpose - Cecilia Agudelo Valderrama (Universidad Autónoma de Madrid, 2018)
Since the creation of the General Education Law in 1994, education authorities have maintained that Colombia has embarked in an education revolution and that schools have curricular autonomy to quality of the education offered to the community. Teachers have been called to become permanent builders of this curriculum; which should be grounded in the idea of creating citizens able to critiqueas one of the ultimate ends of education. The results of this study - focused in the conceptions of 13 math professors for algebra teaching, said individuals had had a varied professional experience and worked in both private and public institutions.- show a different reality. Teachers emphasized their purpose of preparing students to be able to master symbolic expressions as a prerequisite to further courses and to improve their performance in the ICFES exams. These findings speak to us about the why of the identified gap, and warn about the need of creating crucial conditions for change in the educational system; and to provide real development and empowerment opportunities to the teachers.